2020
DOI: 10.3389/fgene.2019.01338
|View full text |Cite
|
Sign up to set email alerts
|

Biology of Tendon Stem Cells and Tendon in Aging

Abstract: Both tendon injuries and tendinopathies, particularly rotator cuff tears, increase with tendon aging. Tendon stem cells play important roles in promoting tendon growth, maintenance, and repair. Aged tendons show a decline in regenerative potential coupled with a loss of stem cell function. Recent studies draw attention to aging primarily a disorder of stem cells. The micro-environment ("niche") where stem cells resided in vivo provides signals that direct them to metabolize, self-renew, differentiate, or remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 131 publications
(231 reference statements)
0
59
0
Order By: Relevance
“…with IL-1β, has been shown to increase tenocyte migration and proliferation, the capacity for which decreases with age. 80,83,87,88,[100][101][102][103][104][105][106] In this study, we observed a decrease in tenocyte migration and proliferation following inflammatory stimulation in all species (statistically significant for sheep tenocyte proliferation as well as rat and mouse tendon cell migration under constant inflammation) except rats (non-significant trend toward increased proliferation), which may be due to our use of tenocytes from individuals in diseaserelevant age groups. The overall gene expression of human tenocytes was most similar to murine under healthy, equine under transient and ovine under constant inflammatory conditions.…”
Section: Discussionmentioning
confidence: 61%
“…with IL-1β, has been shown to increase tenocyte migration and proliferation, the capacity for which decreases with age. 80,83,87,88,[100][101][102][103][104][105][106] In this study, we observed a decrease in tenocyte migration and proliferation following inflammatory stimulation in all species (statistically significant for sheep tenocyte proliferation as well as rat and mouse tendon cell migration under constant inflammation) except rats (non-significant trend toward increased proliferation), which may be due to our use of tenocytes from individuals in diseaserelevant age groups. The overall gene expression of human tenocytes was most similar to murine under healthy, equine under transient and ovine under constant inflammatory conditions.…”
Section: Discussionmentioning
confidence: 61%
“…However, due to the limited availability of these cells, they must be culture expanded. Unfortunately, in vitro expansion has been reported to cause the cells to lose their phenotypic markers [189] and studies have demonstrated that the number of TDSCs are greatly reduced with aging, showing diminished proliferative capacity [190,191]. With this in mind, other cell sources are being investigated for therapeutic use.…”
Section: Stimulating Tendon and Ligament Repairmentioning
confidence: 99%
“…Moreover, it has been reported that the regenerative capacity of aged cells can be restored when exposed to a young environment. These findings suggest opportunities to reverse the aging process of tissues by targeting their niche (Lui and Wong, 2020). As such, MSC-based strategies isolated from neonatal sources might represent promising therapeutic tools for tendon repair and regeneration (Sevivas et al, 2018).…”
Section: Introductionmentioning
confidence: 97%